DNA microbeads for spatio-temporally controlled morphogen release within organoids - Afting, Cassian; Walther, Tobias; Drozdowski, Oliver; Schlagheck, Christina; Schwarz, Ulrich S.; Wittbrodt, Joachim; Göpfrich, Kerstin (Nature nanotechnology, 2024)
Organoids are transformative in vitro model systems that mimic features of the corresponding tissue in vivo. However, across tissue types and species, organoids still often fail to reach full maturity and function because biochemical cues cannot be provided from within the organoid to guide their development. Here we introduce nanoengineered DNA microbeads with tissue mimetic tunable stiffness for implementing spatio-temporally controlled morphogen gradients inside of organoids at any point in their development. Using medaka retinal organoids and early embryos, we show that DNA microbeads can be integrated into embryos and organoids by microinjection and erased in a non-invasive manner with light. Coupling a recombinant surrogate Wnt to the DNA microbeads, we demonstrate the spatio-temporally controlled morphogen release from the microinjection site, which leads to morphogen gradients resulting in the formation of retinal pigmented epithelium while maintaining neuroretinal cell types. Thus, we bioengineered retinal organoids to more closely mirror the cell type diversity of in vivo retinae. Owing to the facile, one-pot fabrication process, the DNA microbead technology can be adapted to other organoid systems for improved tissue mimicry.
Gesehen am 18.09.2024